MANAJEMEN KONFLIK DALAM ORGANISASI (Konsep, Fenomena dan Cara Mengelola Konflik di Lembaga Pendidikan) - Mulhimah, Mulhimah (Jurnal Studi Agama dan Masyarakat, 2014)
Conflict is something that can not be avoided. Even during life , people always confronted and wrestled with the conflict . Likewise with organizational life . Organissai members are always faced with a conflict .. Along with the development of science and technology , there are many changes in social and cultural growth are not the same , so the appearance of disharmony , disintegration and disorganization of society , which contain a variety of open conflict . Such conditions can erode and eliminate human relationships more intimate where people tend to accentuate egoism . Social contacts become fragmented into factions that will ultimately facilitate the emergence of conflict . Conflict management is very influential for the organizations members . Leaders of the organization are required to master conflict management so that the conflicts that arise can have a positive impact on improving the quality of the organization